2003
DOI: 10.1161/01.cir.0000079170.10579.dc
|View full text |Cite
|
Sign up to set email alerts
|

N -Terminal Pro–Brain Natriuretic Peptide and Other Risk Markers for the Separate Prediction of Mortality and Subsequent Myocardial Infarction in Patients With Unstable Coronary Artery Disease

Abstract: Background-Biochemical markers are useful for prediction of cardiac events in patients with non-ST-segment-elevation acute coronary syndrome (ACS). The associations between N-terminal pro-brain natriuretic peptide (NT-proBNP) and other biochemical and clinical risk indicators, as well as their prognostic value concerning the individual end points of death and myocardial infarction (MI), were elucidated in a large cohort of ACS patients. Methods and Results-NT-proBNP, troponin T, and C-reactive protein (CRP) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
3
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(132 citation statements)
references
References 26 publications
(13 reference statements)
8
117
3
4
Order By: Relevance
“…Observational studies have found that CKD is associated with poor in‐hospital, short‐term, and long‐term outcomes among patients with NSTEMI 23, 24, 25. In addition, some observational trials have shown that the outcomes of undergoing PCI are worse in patients with CKD compared with patients with normal renal function 26, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found that CKD is associated with poor in‐hospital, short‐term, and long‐term outcomes among patients with NSTEMI 23, 24, 25. In addition, some observational trials have shown that the outcomes of undergoing PCI are worse in patients with CKD compared with patients with normal renal function 26, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports indicating that the plasma BNP level obtained in the acute phase of AMI can be used as a prognostic marker for patients with AMI [31][32][33][34][35][36][37] ; however, there are no reports on sampling at 3 to 4 weeks after the onset of AMI. In the present study, we performed BNP sampling at 3 to 4 weeks after AMI onset.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the incidences of outcomes differ between patients with HF8 and patients with a recent ACS9 in a stable phase, it is less established how natriuretic peptides are associated with cardiovascular outcomes, especially subsequent MI and stroke, in the latter population 3, 10, 11, 12, 13, 14. Concentrations of natriuretic peptides may be affected by both asymptomatic myocardial ischemia15, 16 and atrial fibrillation,17, 18 which could make BNP and NT‐proBNP relevant as predictors of MI and stroke.…”
Section: Introductionmentioning
confidence: 99%